9.3 FUNCTIONAL AORTIC CHANGES INDUCED BY A HIGH SALT DIET - Kathleen Connolly; Mark Butlin; Bart Spronck; Carmel McEniery; Alberto Avolio; Ian Wilkinson (Artery Research, 2016)
Objective: This study examines effects of high salt diet on arterial blood pressure and aortic function in rats. Methods: Sprague-Dawley rats were fed either high salt content chow or normal chow from weaning. Weight, tail-cuff systolic blood pressure (SBP), water and food intake, and urine output were measured with age. At 16 weeks, rats were anaesthetised and thoracic and abdominal aortic blood pressure measured across a mean arterial pressure range of 60 to 150 mmHg, induced via intra-venous infusion of phenylephrine and sodium nitroprusside. Aortic pulse wave velocity (aPWV) and thoracic to abdominal aortic pulse pressure amplification (PPA) were calculated. Post-mortem weights of the left ventricle and kidneys were recorded. Statistical comparison between groups across the blood pressure range was by robust analysis of covariance. Results: Rats on a high salt diet had lower weights (p=0.04) but similar body mass index. Food intake was similar whilst water intake was greater on a high salt diet, with correspondingly greater urine output. Tail-cuff SBP was higher in rats on a high salt diet. There was no left ventricular hypertrophy (p=0.16) but greater kidney mass in high salt rats (p=0.01). High salt diet resulted in higher aPWV (p<0.001 at each 5 mmHg interval) and PPA (p<0.001 at each 5 mmHg interval). Conclusions: High salt diet induced a moderate increase in arterial blood pressure, increased aortic stiffness, and higher PPA, indicating marked changes in transmission characteristics of the aorta including altered stiffness gradient and changed peripheral wave reflection characteristics.